Design and inception of a study to explore putative links between migraine, appetite behaviours and obesity in children. (29th September 2015) - Ray, S; Singh, S; Curran, A; Halford, J; Harrold, J; Kumar, R
Abstract : Aim: To discuss the hypothesis, design and early experiences following inception of an ongoing pilot study of migraine and appetite behaviours in children. Background: Recent research has highlighted an association between migraine and obesity, including in children. A causal relationship, and its direction, is not established. There are overlapping neurobiological mechanisms in migraine, appetite behaviour and obesity. Migraine has been noted to affect appetite behaviours, but this has not been formally studied previously. The authors wish to explore the biologically plausible hypothesis that migraine may lead to obesity, via alterations of appetite and food intake. Method: Initial literature search and hypothesis generation started in 2008. A collaboration between the clinical paediatric neurology service and the university-based biopsychology research group was formed. A single-centre, cross-sectional, questionnaire-based, clinical migraine population pilot study was designed. The primary outcome is association between measures of migraine severity and eating behaviour using validated tools. Secondary outcomes are to classify, describe and quantify appetite behaviour in paediatric migraineurs including food cravings. Specific tools used are the PedMIDAS, Dutch Eating Behaviour Questionnaire, Child Eating Behaviour Questionnaire, Child Behavior Checklist, Food Cravings Inventory and a food intake questionnaire. The sample size appropriate for a pilot study was 60 children with migraine, and 30 non-migraine headache controls. The main exclusion criterion is current treatment with migraine prophylaxis medications. Results: Local research ethics and Trust R&D approvals were granted in June 2009. Recruitment from the paediatric neurology and general paediatric clinics commenced July 2009. The study is on-track for completion by mid-2010. Early qualitative experience in performing the study includes issues such as some limitations of the questionnaires and tools used, the PedMIDAS in particular.